2002
DOI: 10.1034/j.1600-0447.2002.02220.x
|View full text |Cite
|
Sign up to set email alerts
|

Classification of obsessive‐compulsive disorder in childhood and adolescence

Abstract: This study suggests that the DSM-IV criteria are superior to that of ICD-10-DCR for diagnosing OCD in children and younger adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Focussing on the positive diagnoses, the DSM-IV-TR consistently classified more children with an anxiety disorder than the ICD-10 for SAD, GAD, social and specific phobia. Results are comparable to previous studies comparing ICD-10 and DSM-IV diagnoses of mental disorders in children and adolescents [14,16]. …”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Focussing on the positive diagnoses, the DSM-IV-TR consistently classified more children with an anxiety disorder than the ICD-10 for SAD, GAD, social and specific phobia. Results are comparable to previous studies comparing ICD-10 and DSM-IV diagnoses of mental disorders in children and adolescents [14,16]. …”
Section: Discussionsupporting
confidence: 86%
“…Steinberger and Schuch [14] examined the diagnostic concordance for 66 children with obsessive-compulsive disorder (OCD) using semi-structured instruments, the International Diagnostic Checklists for DSM-IV and ICD-10 IDCL, [15]. They found evidence of poor agreement between the two classification systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Establishing a diagnosis of OCD can be done using the Diagnostic and Statistical Manual of Mental Disorders, 4 th edition (APA, 1994), known as the DSM‐IV, and the International Statistical Classification of Diseases, 10 th edition (World Health Organization [WHO], 1992), known as the ICD‐10. Steinberger and Schuch (2002) compared the suitability of the DSM‐IV and ICD‐10 diagnostic criteria in a clinical sample of children and adolescents with OCD. The authors found a poor agreement between the diagnostic concepts of the DSM‐IV and ICD‐10.…”
Section: Assessment Tools and Diagnostic Classificationmentioning
confidence: 99%